An Account on a Social Network Site as a Site of Memory. Memory in the Internet Fake, Like and Hate. A New Expression of Polish Patriotism? - Ratke-Majewska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of the article is - firstly - to get an answer to the question of what image of Polish patriotism is offered by the Internet fake, like and hate, and secondly - to reflect on its causes and consequences for the Polish community. The text presents the results of the autor`s own research with comments and conclusions. The presented research relied, in turn, on the content analysis of the memory narratives constructed by users of Polish patriotic accounts functioning on Facebook. More importantly, the analyses focused on both formal issues (the number of sites and their popularity), as well as substantive ones (issues discussed within a given website, threads raised and users` opinions).
Keywords: Internet social network; fake; like and hate; memory; Polish patriotism